Molecular Interactions Driving Intermediate Filament Assembly - Vermeire, Pieter-Jan; Stalmans, Giel; Lilina, Anastasia V; Fiala, Jan; Novak, Petr; Herrmann, Harald; Strelkov, Sergei V (Cells, 2021)
Given the role of intermediate filaments (IFs) in normal cell physiology and scores of IF-linked diseases, the importance of understanding their molecular structure is beyond doubt. Research into the IF structure was initiated more than 30 years ago, and some important advances have been made. Using crystallography and other methods, the central coiled-coil domain of the elementary dimer and also the structural basis of the soluble tetramer formation have been studied to atomic precision. However, the molecular interactions driving later stages of the filament assembly are still not fully understood. For cytoplasmic IFs, much of the currently available insight is due to chemical cross-linking experiments that date back to the 1990s. This technique has since been radically improved, and several groups have utilized it recently to obtain data on lamin filament assembly. Here, we will summarize these findings and reflect on the remaining open questions and challenges of IF structure. We argue that, in addition to X-ray crystallography, chemical cross-linking and cryoelectron microscopy are the techniques that should enable major new advances in the field in the near future.
Keywords: cytoskelet; Cell Physiological Phenomena; assembly; fyziologie buňky; intermediární filamenta; lamin; Cytoskeleton; intermediate filament; Animals; vimentin; lidé; keratin; Intermediate Filaments; X-ray crystallography; chemical analytical cross-linking; Humans; zvířata; cryoelectron microscopy